2018
DOI: 10.1016/j.clml.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Consolidative Radiotherapy to Residual Masses After Chemotherapy Is Associated With Improved Outcome in Diffuse Large B-Cell Lymphoma. A Retrospective, Population-Based Study

Abstract: With the limitations of a retrospective study, these data suggest that consolidative RT might improve survival in DLBCL patients with a residual mass after chemotherapy, also in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…12 In Norway, researchers reported improved outcome among patients with any residual mass and RT vs no RT, but it was not evident in patients who were considered high-risk (IPI 4-5). 25 Recently published results of randomized study found that R-CHOP alone is not inferior compared to R-CHOP + RT among patients with limited-stage disease and without bulky tumor. This study included iPET as an evaluation method for all patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…12 In Norway, researchers reported improved outcome among patients with any residual mass and RT vs no RT, but it was not evident in patients who were considered high-risk (IPI 4-5). 25 Recently published results of randomized study found that R-CHOP alone is not inferior compared to R-CHOP + RT among patients with limited-stage disease and without bulky tumor. This study included iPET as an evaluation method for all patients.…”
Section: Discussionmentioning
confidence: 98%
“…According to Pfreundschuh et al, results from OPTIMAL > 60 study, it seems that RT can be spared from patients with bulky but negative iPET after chemotherapy without compromising the results . In Norway, researchers reported improved outcome among patients with any residual mass and RT vs no RT, but it was not evident in patients who were considered high‐risk (IPI 4‐5) . Recently published results of randomized study found that R‐CHOP alone is not inferior compared to R‐CHOP + RT among patients with limited‐stage disease and without bulky tumor.…”
Section: Discussionmentioning
confidence: 99%
“…40 Previously published retrospective analyses, most performed in the absence of functional imaging for response assessment, have suggested benefit conferred by the use of routine consolidative RT in advanced DLBCL, in addition to its application to certain extranodal sites, in particular skeletal involvement. 9,10,17,18,[41][42][43][44] As a result, there are recommendations that continue to endorse RT in these patients. 7,13,45 We acknowledge that there are centers that have changed their practice in the modern era and have already adopted a similar PET-guided algorithm, omitting RT in patients with PET-NEG scans at EOT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact definition of bulky disease is still under debate, ranging between 5 and 10 cm, it has been proven that RT contributes significantly to locoregional control (LRC) and survival for patients with bulky or residual disease after chemotherapy [18,[21][22][23][24]. In multivariate analysis, bulky disease was associated with better PFS and OS (HR=0.02, p=0.009) [18].…”
Section: Bulky or Residual Diseasementioning
confidence: 99%
“…In multivariate analysis, bulky disease was associated with better PFS and OS (HR=0.02, p=0.009) [18]. Øystein Fluge et al analysed 211 DLBCL patients and divided patients into complete remission (CR) group (n=73) and any residual mass group (n=138), which included partial response (PR) and CR unconfirmed (Cru) [23]. Among 138 patients with any residual mass after chemotherapy, 57 patients did not receive RT and 81 patients received RT.…”
Section: Bulky or Residual Diseasementioning
confidence: 99%